Peran Konselor Islami dalam Membantu Klien Mengoptimalkan Potensi Akal Menurut Al Quran - Betri Yulita Betri yulita (JURNAL KONSELING GUSJIGANG, 2020)
This study aims to determine the task of a counselor in helping clients optimize their abilities or potential for reason. The development of human potential to be productive and useful will be achieved if it continues to be sharpened according to ability and directed to positive and beneficial things. Potential possessed by humans if not used properly, will cause problems in humans themselves. The method in this research is library research method. The results obtained from research data sources are about the role of counselors in helping clients that is directing the potential of the client in order to support its development, in line with the purpose of counseling that is to establish the client in accordance with its potential.